Extraction of Zanthoxylum seed protein and identification of its simulated digestion products. (1st May 2022) - Luo, Qingying; Li, Xiaomeng; Zhang, Zhiqing; Chen, Anjun; Li, Shanshan; Shen, Guanghui; Li, Meiliang; Liu, Xingyan; Yin, Xueqin; Cheng, Lan; Yang, Xingpan; Jiang, Chunping; et al.
Abstract: Zanthoxylum bungeanum seed is the main by-product of Z. bungeanum processing, which is rich in protein. In this study, Z. bungeanum seed proteins were extracted by alkali-soluble acid precipitation method. The factors affecting the protein yield were ranked as follows: alkali dissolution temperature > extraction time > material–liquid ratio > pH. The optimal process conditions were as follows: extraction temperature 40 °C, extraction time 40 min, material–liquid ratio 1:20 (w/v) and pH 10. Under these conditions, the yield of Z. bungeanum seed protein reached 33.40%. The results of a series of antioxidant assays showed that the molecular weight of digestion products was mainly concentrated within 1200 Da, and the strongest signal response was 373.25 Da. In addition, the antioxidant activity of digestive products increased throughout the digestion process. Nano LC-ESI-MS/MS technology and bioinformatics databases were combined to identify and predict all peptides in the final product of simulated digestion. Sixty-six suspected bioactive peptides were obtained. Amongst them, 51 had antibacterial activity, 1 had nerve-blocking effect, 6 had growth-factor-like function, 3 had anticancer activity, 4 had antiviral activity, and 1 had drug delivery function. Highlights: The simulated digestion products were systematically analysed for the first time. Sixty-six suspected bioactive peptides could be obtained from the simulated digestion. The simulated digestion products had antioxidant activity. Mass spectrometry and bioinformatics tools were used to find new bioactive peptides.